The European skill space: a cross-country analysis of path-dependent capability development - Sonja Walter; Wonsub Eum; Jeong-Dong Lee (Baltic Journal of Economics, 2024)
This study investigates the skill structures of European countries and their transformations from the perspective of capability development. The constructed skill space illustrates the skill sets of European nations based on product space methodology by linking skill occupation and occupation–country data from 2011 to 2018. The results show that there are remarkable differences in skill structures among countries, and there is a strong path dependence in skill development. The findings suggest that skill convergence is unlikely to occur and that skill inequality among countries requires serious consideration.